Cost-Effectiveness of Physical Rehabilitation and Care of Older Home-Dwelling Persons after Hip Fracture: A Systematic Review and Narrative Synthesis - Jonas Ammundsen Ipsen; Lars T. Pedersen; Eva Draborg; Inge H. Bruun; Charlotte Abrahamsen; Bjarke Viberg (Medical Journals Sweden, 2022)
Objective: To provide a systematic review of the literature and knowledge base of cost per quality-adjusted life year of physical rehabilitation and care of older persons after hip fracture. Material and methods: A research librarian assisted in searching 9 databases (14 May to 27 May 2021), with exclusion of studies on cognitively impaired or institutionalized individuals. A stepwise selection process was conducted by 2 authors, study quality was assessed using Drummond et al.'s checklist, and comparison between different countries was assessed using Welte et al.'s checklist. Results: Three studies were included, which employed 3 different interventions initiated at 3 different postoperative time-points. One high-quality study demonstrated that comprehensive geriatric assessment was cost-effective compared with coordinated care. The other 2 studies did not find the interventions studied to be cost-effective, and both studies were deemed to be of moderate quality. Conclusion: The body of evidence on the cost-effectiveness of physical rehabilitation and care after hip fracture is limited and heterogeneous, with only 1 high-quality study. Thus, stakeholders perform decision-making with a limited knowledge base of the cost-effectiveness of physical rehabilitation and care. We recommend researchers to assess cost-per-QALY. LAY ABSTRACT Hip fractures have severe consequences for older persons and, after surgery, patients need physical rehabilitation and care to recover. Physical rehabilitation and care vary greatly in terms of effectiveness and cost. It is not known what kind of physical rehabilitation and care contribute most to health relative to their costs. This systematic review provides the first comprehensive description of the cost- effectiveness of physical rehabilitation and care of older persons after hip fracture. Nine databases were searched, and 3 economic evaluation studies were identified. One economic study identified comprehensive geriatric care as cost-effective compared with usual coordinated care. The other two studies consisting of an intervention of additional 10 weeks of physical rehabilitation initiated 4 months after discharge and an intervention physical rehabilitation and nutrient management proved not cost-effective compared to usual rehabilitation and care. In conclusion, the number of studies published in this field is very limited and further research is necessary.